1998
DOI: 10.1021/bi9726180
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Assembly on Telomeric Sequences

Abstract: The organization of telomeric chromatin differs from that of bulk chromatin in some peculiar features, such as the unusually short nucleosomal spacing found in vertebrates. Telomeric DNAs are straight, since they consist mostly of 6-8-bp repeated sequences, therefore out of phase with the B DNA period. This feature should be of relevance in nucleosome formation, suggesting the usefulness of studying simple model systems of nucleosome assembly. We reconstituted nucleosomes in vitro, by using purified histone oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…Nucleosome assembly on the telomeric sequences from various organisms has been extensively analyzed, by competitive reconstitution assays in vitro (4,(9)(10)(11). These studies revealed that all telomeric sequences tested show comparative positive free energies in nucleosome formation, relative to average nucleosomal DNA.…”
Section: Nucleosome Formation With Telomeric Repeat Sequences In Vitromentioning
confidence: 99%
“…Nucleosome assembly on the telomeric sequences from various organisms has been extensively analyzed, by competitive reconstitution assays in vitro (4,(9)(10)(11). These studies revealed that all telomeric sequences tested show comparative positive free energies in nucleosome formation, relative to average nucleosomal DNA.…”
Section: Nucleosome Formation With Telomeric Repeat Sequences In Vitromentioning
confidence: 99%
“…Differential free energy data were collected by different authors for synthetic and natural DNA tracts with different length and intrinsic curvatures [32][33][34][35][36][37][38][40][41][42][43][44][45][46][47][48][49] as well as sequences with virtually highest affinity as obtained by SELEX procedures [39]. Despite the DNA tracts investigated are characterized by a variety of sequences, lengths and curvatures, the free energy range is limited to a few kilocalories per nucleosome.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Despite the DNA tracts investigated are characterized by a variety of sequences, lengths and curvatures, the free energy range is limited to a few kilocalories per nucleosome. It is interesting to note that the free energies involved in nucleosome formation on the telomeres are the highest among the synthetic and biological sequences investigated so far [38,40,41,[45][46][47].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the double-stranded telomeric DNA is packed with histone octamers in nucleosomes (Tommerup et al 1994), whereas a nonnucleosomal structure termed the telosome (Wright et al 1992) may be present only at telomere ends (Lingner & Cech 1998). Studies of telomeric chromatin have shown its speci c features: on the one hand a lack of nucleosome positioning, and on the other hand a speci c and very short nucleosome spacing as revealed by micrococcal nuclease digestion (Fajkus et al 1995;Makarov et al 1993;Rossetti et al 1998). On the basis of these properties and on accumulated experimental data, we proposed a model for a columnar packing of nucleosomes in telomeric chromatin in which the DNA is continuously wound in a parallel manner around the stacked histone cores (Fajkus & Trifonov 2001).…”
Section: Human Telomere Structure and Functionmentioning
confidence: 99%